Impact of food processing on the allergenic properties of amylase trypsin inhibitors from wheat - Weegels, Peter L.; America, Antoine H. P. (Frontiers in Allergy, 2023)
Amylase trypsin inhibitors (ATIs) play an important role in wheat allergies and potentially in non-coeliac wheat sensitivity. Food processing could be important to mitigate the pathogenic properties of ATIs, e.g., by denaturation, glycation, enzymatic hydrolysis, cross-linking, and oxidation and reduction. These modifications also impact the solubility and extractability. The complex solubility behaviour of ATI isoforms (water and salt soluble, but also chloroform–methanol soluble, solubility depending on the redox state) becomes even more complex upon processing due to denaturation and (bio)chemical modifications. This significantly hinders the feasibility of quantitative extraction. Moreover, changes in biofunctionality may occur during the process of extraction, and the changes in ATI due to food processing will be more difficult to assess. Heat treatment decreases the extractability of ATIs with water, NaCl, and other buffer extracts, and binding of IgE from wheat-allergic persons to ATIs as observed with Western blotting is decreased or absent. IgE binding is reduced with the total extract in chaotropic and reducing agents. However, it can be increased when the proteins are hydrolyzed by proteases. Fermentation involving certain species of Fructolactobacilli (FLB), followed by baking, decreases the amount of ATIs and IgE binding to ATIs. In yeast-fermented bread, the amount of ATIs decreased in a similar manner, but IgE binding was more prominent, indicating that there was a modification of ATIs that affected the epitope recognition. When isolated ATIs are ingested with high ATI degrading FLB, the immune response in mice is less elevated in vivo, when compared with ATI without high ATI degrading FLB. The pathogenic effects on the skin of dogs and one wheat-allergic child are also decreased when soluble proteins or isolated ATIs are reduced with the thioredoxin/thioredoxin reductase NADPH system. Glycation on the other hand has been shown to potentiate the allergenic properties of ATIs as evidenced by the large increase in IgE binding. The impact of food processing on the pathogenic properties of ATIs is hardly studied in vivo in humans. There seem to be opportunities to mitigate the pathogenic properties in vitro, but potentiation of pathogenic properties is also frequently observed. This requires a deeper understanding on the impact of food processing on the pathogenicity of ATIs.